Psychosocial determinants of the intention and self-efficacy to attend antenatal appointments among pregnant adolescents and young women in Cape Town, South Africa: a cross-sectional study - Ronel Sewpaul; Rik Crutzen; Priscilla Reddy (BMC, 2022)
Abstract Background Antenatal care is imperative for adolescents and young women, due to their increased risk of pregnancy-related complications. Evidence on the psychosocial determinants of antenatal attendance among this vulnerable group is lacking. This study assessed the relevance of the psychosocial sub-determinants of intention and self-efficacy to attend antenatal appointments among pregnant adolescents and young women in Cape Town, South Africa; with a view to informing behaviour change interventions. Methods Pregnant women and girls aged 13-20 years were recruited to complete a cross-sectional questionnaire assessing their pregnancy experiences, pregnancy-related knowledge and psychosocial determinants related to antenatal care seeking. Confidence Interval Based Estimation of Relevance (CIBER) analysis was used to examine the association of the psychosocial sub-determinants with the intention and self-efficacy to attend antenatal appointments, and to establish their relevance for behaviour change interventions. The psychosocial sub-determinants comprised knowledge, risk perceptions, and peer, partner, family and individual participant attitudes. Results The mean gestation age of participants (n=575) was 18.7 weeks, and the mean age was 18 years. Risk perceptions of experiencing preeclampsia and heavy bleeding during pregnancy or childbirth if clinic appointments are not attended had moderate mean scores and were positively correlated with intention and self-efficacy, which makes them relevant intervention targets. Several family, peer, partner and individual participant attitudes that affirmed timely appointment attendance had strong positive associations with intention and self-efficacy but their mean score were already high. Conclusions Given the high means of the family, peer, partner and individual participant attitudes, the relevance of these attitudinal items as intervention targets was relatively low. Further studies are recommended to assess the relevance of these sub-determinants in similar populations.